Composition Characterization of Fatty Acid Zinc Salts by Chromatographic and NMR Spectroscopic Analyses on Their Fatty Acid Methyl Esters - Kwang Seo Park; Yun Ju Kim; Eun Kyung Choe (Journal of Analytical Methods in Chemistry)
To implement EU REACH- (Registration, Evaluation, and Authorization of Chemicals-) like chemical legislations in various countries of which the purpose is human and environment safety, the first step is substance identification followed by the hazard and risk assessments. Although both structural and composition identifications are required, the latter can more importantly result in the essential data to fill out the required substance information such as purity and concentrations of constituents, as well as impurities. With fatty acid zinc salts (FAZSs) as an exemplary industrial chemical of which chromatographic and nuclear magnetic resonance (NMR) analyses were impossible due to their insolubility in water and any organic solvents, the composition characterization was tried by preparing their fatty acid methyl esters (FAMEs) using the conc. HCl/methanol/toluene method. This acid-catalyzed methyl esterification was optimized with zinc stearate as a surrogate substance. Gas chromatography-mass spectrometry (GC-MS) and NMR analyses on methyl-esterified products revealed that the optimum conditions were at 90°C for 10 min or 45°C for 30 min with two equivalent HCl as well as at 45°C for 10 min with five equivalent HCl. Almost all zinc stearates were converted into the corresponding fatty acids with 97–99% conversion rates. Free fatty acids (FFAs) were detected in extracted ion chromatograms of pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) in the methyl-esterified products with incomplete conversions of 73∼79%. The optimized conc. HCl/methanol/toluene method of direct one-step reaction from FAZSs was compared with the two-step NaOH saponification/BF3-methanol method after acidic hydrolysis of FAZSs. The mechanism of fatty acid zinc salts into free fatty acids and fatty acid methyl esters was suggested with the evidence of the formation of Zn(OH)2.